2018
DOI: 10.1124/jpet.118.247767
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro–In Vivo Extrapolation of OATP1B-Mediated Drug–Drug Interactions in Cynomolgus Monkey

Abstract: Hepatic organic anion-transporting polypeptides (OATP) 1B1 and 1B3 are clinically relevant transporters associated with significant drug-drug interactions (DDIs) and safety concerns. Given that OATP1Bs in cynomolgus monkey share >90% degree of gene and amino acid sequence homology with human orthologs, we evaluated the in vitro-in vivo translation of OATP1B-mediated DDI risk using this preclinical model. In vitro studies using plated cynomolgus monkey hepatocytes showed active uptake K values of 2.0 and 3.9 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 43 publications
4
27
1
Order By: Relevance
“…All procedures performed on these animals were in accordance with regulations and established guidelines, were reviewed and approved by Pfizer Institutional Animal Care and Use Committee, and were conducted at Pfizer (Groton, CT). Male cynomolgus macaque Mauritian monkeys (6-9 years of age) were used, and the procedures similar to those previously reported were adopted with some modifications (Varma et al, 2017b;de Bruyn et al, 2018;Ufuk et al, 2018). A crossover study design was employed, in which the same four animals were dosed over all studies, following a minimum 1-week washout period between each study.…”
Section: Methodsmentioning
confidence: 99%
“…All procedures performed on these animals were in accordance with regulations and established guidelines, were reviewed and approved by Pfizer Institutional Animal Care and Use Committee, and were conducted at Pfizer (Groton, CT). Male cynomolgus macaque Mauritian monkeys (6-9 years of age) were used, and the procedures similar to those previously reported were adopted with some modifications (Varma et al, 2017b;de Bruyn et al, 2018;Ufuk et al, 2018). A crossover study design was employed, in which the same four animals were dosed over all studies, following a minimum 1-week washout period between each study.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, an analogous approach was applied here to two widely used preclinical species, beagle dog and Sprague-Dawley rat. As a nonrodent preclinical species, beagle dogs are often used in pharmacokinetic studies; however, there is less information available to assess the predictive performance of hepatic transportermediated clearance and DDIs in this species compared with studies reported in cynomolgus monkeys (Shen et al, 2013;Chu et al, 2015;Watanabe et al, 2015;Ufuk et al, 2018). Therefore, characteristics of the hepatic uptake of a series of nine drugs were investigated to provide a data set of parameters for comparative purposes and evaluate beagle dogs as a preclinical animal model to study hepatic uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated the utility of the cynomolgus monkey as a preclinical species for evaluation of organic anion transporting polypeptide (OATP)-mediated hepatic clearance and DDIs (De Bruyn et al, 2018;Ufuk et al, 2018). Despite an overall good relationship between in vitro-derived clearance in cynomolgus monkey hepatocytes and in vivo clearance in the same species, the underprediction trend was apparent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OATP1B1, OATP1B3 and OATP2B1 are also expressed in the liver of cynomolgus monkeys, in a manner similar to humans (Hirano, Maeda, Shitara, & Sugiyama, 2006;Takahashi et al, 2013). To predict clinical drug interactions mediated by hepatic OATPs, cynomolgus monkey models have also been proposed (Shen et al, 2013;Takahashi et al, 2013;Ufuk et al, 2018;Watanabe, Watanabe, Yabuki, & Tamai, 2015). Substrate recognition for human OATP1B1, OATP1B3 and OATP2B1 has been extensively reported and is summarized in Table 1.…”
mentioning
confidence: 99%